2011
DOI: 10.1111/j.1949-8594.2010.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Teacher‐Facilitated, Inquiry‐Based Instruction to Student Higher‐Order Thinking

Abstract: Commissions, studies, and reports continue to call for inquiry‐based learning approaches in science and math that challenge students to think critically and deeply. While working with a group of middle school science and math teachers, we conducted more than 100 classroom observations, assessing several attributes of inquiry‐based instruction. We sorted the observations into two groups based on whether students both explored underlying concepts before receiving explanations and contributed to the explanations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 2 publications
1
55
1
8
Order By: Relevance
“…IBL is one method that employs active group learning [21]. IBL reduces the gap between subgroups of students (gender, race, socioeconomic status, learning needs, and language learners).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBL is one method that employs active group learning [21]. IBL reduces the gap between subgroups of students (gender, race, socioeconomic status, learning needs, and language learners).…”
Section: Resultsmentioning
confidence: 99%
“…As educators, we need to expect more of our students by providing them with challenging inquiry tasks, encouraging them to collaborate with classmates, and supporting them to achieve amazing results. Marshall and Horton [21] report that students who sit and listen to lectures and participate in rote learning are less likely to be involved in critical thinking activities. Their study showed higher-level thinking and learning takes place when traditional class time is substituted with student exploration activities in mathematics or science classes.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of teacher direction in inquiry based learning is a critical factor in determining the level or category of the inquiry model. Confirmation or pre-inquiry level models are characterised by high levels of teacher direction and correspondingly low levels of student direction, whereas in open or exemplary inquiry models, each stage of the inquiry process is student directed (Bell, Smetana, and Binns 2005;Zion, Cohen, and Amir 2007;Banchi and Bell 2008;Marshall and Horton 2011). In other words, students identify a problem or pose a question, propose an explanation or solution, choose a method to test their proposal or answer their question and, through the process of inquiry, extend their knowledge and develop deep conceptual understandings (Bell, Smetana, and Binns 2005;Zion, Cohen, and Amir 2007;Banchi and Bell 2008).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The literature gives a few IBL models and they are primarily based on three key indicators, which describe the nature of the research: the initial level of knowledge, attention to the learning process and workload (in the class, throughout the course and in life as a whole). All of the IBL models are identified according to the following criteria (Minner et al, 2010;Marshall & Horton, 2011;Levy et al, 2012): (1) the research approval, (2) the query structure, (3) directing the research, (4) research openness, (5) the research variations. Well-designed IBL environment can enhance students' learning experience (Goldston et al, 2010;Mountrakis & Triantakonstantis, 2012).…”
Section: Theoretical Basismentioning
confidence: 99%